Space-Time Evolution Laws of Zonal Disintegration in Deep Underground Caves Based on Coordination Deformation between the Bolt Body and Surrounding Rock - Yuan-xiang Yu; Zhi-xun Xie; Bao-ping Chen (Advances in Civil Engineering)
Zonal disintegration refers to the special phenomenon whereby fractured zones and intact zones appear alternately in deep-buried surrounding rocks under high stress conditions, which are different from that of the shallow rock mass. Because the divisional rupture law in engineering practice is closely related to the force characteristics of the bolt body, this paper analyzed stress distribution rules of the same bolt body at different times and that of different bolt bodies at the same time in the case of zonal disintegration based on coordination deformation between the bolt body and surrounding rock. The nonlinear rheological mechanics model of rock mass on the elastic-plastic interface under the maximum support pressure was established. It puts forward the theoretical calculation formula about the mechanics criterion and breakdown moment of the zonal disintegration. Using the mechanics model of interaction between a bolt and the surrounding rock, the distribution locations along the bolt body of the anchor neutral points and its maximum axial forces were discussed with the multiple theoretical neutral points. Furthermore, the location and width of each fracture zone were back analyzed. The results show that the rock mass on the elastic-plastic interface of the surrounding rock has a significant creep effect after the excavation of the deep underground cave. While maximum deviator stress of the rock mass is more than its long-term strength, the rock mass will fracture along a radial direction and come into the fractured zone. The multiple redistribution of the surrounding rock stress will generate alternate distribution phenomena of the fractured zone and intact zone. Meanwhile, the distribution regularity of the peaks and troughs interval of the displacement of surrounding rock leads to multiple neutral points along the anchor length direction. The computed results of zonal disintegration through the back analysis can reflect the actual space-time evolution laws of zonal disintegration in deep underground caves.